2013
DOI: 10.1002/jnm.1921
|View full text |Cite
|
Sign up to set email alerts
|

VHDL‐AMS in switched‐current analog filter pair design based on a gyrator‐capacitor prototype circuit

Abstract: SUMMARYThis paper presents an approach to a low-sensitivity design strategy for switched-current (SI) filter pairs based on a gyrator-capacitor prototype circuit. On the basis of a prototype filter, an SI counterpart circuit is obtained. Tools for SI filter design automation have been developed, which make a hardware description language -analog-mixed signal synthesization for the chosen kind of circuit. The obtained SI filter is better than the filter obtained using LC ladder structures with respect to very-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…. v x nodes and is connected to the suitable node with block of switches SWITCHES 13 or SWITCHES 14 , respectively. The blocks are controlled using W sp and W sm words.…”
Section: Routing Of Arraymentioning
confidence: 99%
See 2 more Smart Citations
“…. v x nodes and is connected to the suitable node with block of switches SWITCHES 13 or SWITCHES 14 , respectively. The blocks are controlled using W sp and W sm words.…”
Section: Routing Of Arraymentioning
confidence: 99%
“…The inductor L was replaced by a gyrator-capacitor circuit (I G1 − C4 − I G2) [13,21]. Parameters of the gyrator-capacitor prototype were calculated using the method proposed in [15].…”
Section: Elliptic Filtermentioning
confidence: 99%
See 1 more Smart Citation
“…W szczególności uwidacznia się to w projektowaniu precyzyjnych filtrów mających swoje zastosowania w wielu różnych aplikacjach związanych z przetwarzaniem sygnału [1,2,3]. Niniejsza praca, na przykładzie układów z przełączanymi prądami, pokazuje nowatorskie podejście do rozwiązania takich problemów, a opisana metoda będzie zilustrowana przykładem pary filtrów pracującej w trybie przełączanych prądów [4]. Należy przede wszystkim zaznaczyć, że właściwości obwodów pracujących w trybie prądowym są mało wrażliwe na obniżanie napięcia zasilającego.…”
Section: Wprowadzenieunclassified
“…In [29] is shown that among analog integrating filters the best properties has the second order filter having two equal real poles. Also are given recommendations how to provide the required accuracy and sufficient decay rate for transients in the filter itself.…”
mentioning
confidence: 99%